골반견인과 골반기울기운동이 요천각에 미치는 영향 - 정해근 (연세대학교 보건대학원, 1989)
[한글] 요통의 원인은 다양하지만 대부분의 요통은 요부 및 요천부 근골격계의 병변으로 인한 역학적 요통이다. 요통치료는 재활의학적인 치료와 외과적인 치료가 있다. 본 연구는 재활의학적인 치료의 일부인 골반 견인치료와 골반 기울기 운동이 요천각의 감소 및 요추간판 간격을 확장시키는가를 확인함을 목적으로 하였다. 이에따라 1988년 3월 1일부터 1989년 4월 1일까지 의 연세의대 영동 세브란스 병원 재활의학과에서 요부 및 요천부 신경근 병변환자 45명을 대상으로 하였다. 치료전과 치료후에 차이가 있는가를 알아보기 위하여 짝비교 t검정을 시행하였다. 본 연구의 결과는 다음과 같다. 1. 요부 및 요천부 신경근 병변환자 총 45명중 33명인 67%가 치료후에 요천각 감소를 보였다. 평균 각도는 5.02도였다. 2. 치료후에 모든 대상에서 요추간판 간격이 증가하였다. 후방 요추간판 평균증가량은 1.2mm였다. L^^4∼L^^5 사이의 후방 요추간판 평균증가량은 1.3mm로 제일 많이 증가하였다. 3. L^^4∼L^^5의 후방 요추간판 간격은 치료기간이 연장됨에 따라 증가하였다. 위의 결과에서 골반 견인과 골반 기울기 운동이 요천각 감소와 요추간판 간격 확장에 중요한 효과가 있었다. 그러므로 본 치료방법은 요천각 감소와 요추간판 간격 확장에 유용한 치료 방법이라고 사료된다. 추후에는 요부 및 요천부 신경근 병변환자 뿐만 아니라 다른 근골격계 병변환자에 관한 연구도 진행되어져야 할 것이다. Effect of pelvic traction and exorcise on the lumbosacral angle and intervertebral disc space HAE GUN CHUHG Graduate School of Health, Science and Management, Yonsei University Seoul, Korea (Directed by professor Jae Ho Moon, H.D.) The purposes of this study were to determine the effects of pelvic traction and exercise on the lumbosacral angle and intervertebral separation in the lumbar spine. The subjects of this study were 45 patients with average age of 34.8 ranging from ]9 to 58 years; 19 were male and 26 femate. All were admitted to the Dept. of Rehabilitation Medicine, Yong Dong Severance Hospital, with a diagnosis of lumber and lmbosacral radiculopathy for the conservative management of lo back pain. All cases received Rehabilitation management in the form of hot pack, ulitrasound, lumbar traction, low back exercise and education for posture in ADL. The results were as follows: 1. Sixty-seven percent of all patients showed fovorable results wish an average decrease of 5.02 degree in the lumbosacral angle. 2. As for vertebral separation in the lumbar spinet there were statistically significant widening of the intervertebral spaces except at the L^^2-L^^3 anterior intervertebral area. The average increase at the posterior areas was 1.2mm. It was 1.3mmm in the L^^4-L^^5 posterior area. 3. The posterior L^^4-L^^5 intervertebral space continued to widen as the number of weeks of treatment progressed, although individual weekly increment gradually decreased. According to the above results, pelvic traction and low back exercise can be considered as significant contributing physical modality in the management of patient with lumbar and lumbosacral radiculopaties. [영문] The purposes of this study were to determine the effects of pelvic traction and exercise on the lumbosacral angle and intervertebral separation in the lumbar spine. The subjects of this study were 45 patients with average age of 34.8 ranging from ]9 to 58 years; 19 were male and 26 femate. All were admitted to the Dept. of Rehabilitation Medicine, Yong Dong Severance Hospital, with a diagnosis of lumber and lmbosacral radiculopathy for the conservative management of lo back pain. All cases received Rehabilitation management in the form of hot pack, ulitrasound, lumbar traction, low back exercise and education for posture in ADL. The results were as follows: 1. Sixty-seven percent of all patients showed fovorable results wish an average decrease of 5.02 degree in the lumbosacral angle. 2. As for vertebral separation in the lumbar spinet there were statistically significant widening of the intervertebral spaces except at the L^^2-L^^3 anterior intervertebral area. The average increase at the posterior areas was 1.2mm. It was 1.3mmm in the L^^4-L^^5 posterior area. 3. The posterior L^^4-L^^5 intervertebral space continued to widen as the number of weeks of treatment progressed, although individual weekly increment gradually decreased. According to the above results, pelvic traction and low back exercise can be considered as significant contributing physical modality in the management of patient with lumbar and lumbosacral radiculopaties.
보건학과/석사